Um estudo sobre modelos Markovianos - Anjos, Vitor Schroeder dos (Universidade Federal de São Carlos, 2024)
Markov chains have a range of applications within modeling, and due to their importance, are greatly studied in the literature. Herein, the objective of this paper is to study first-order Markov chains, presenting the principal concepts and properties related to them, with special attention given to their interpretation. In particular, we will define and explore several aspects associated with the stationary distribution.
A study on Markovian models
Keywords: Cadeias de Markov; Distribuição estacionária; Modelagem; Markov chain; Stationary distribution; Modeling; CIENCIAS EXATAS E DA TERRA::MATEMATICA